Synthesis, toxicity, biocompatibility, and biomedical applications of graphene and graphene-related materials - Gurunathan S (Dove Medical Press, 2016)
Sangiliyandi Gurunathan, Jin-Hoi Kim Stem Cell and Regenerative Biology, Konkuk University, Seoul, Republic of Korea Abstract: Graphene is a two-dimensional atomic crystal, and since its development it has been applied in many novel ways in both research and industry. Graphene possesses unique properties, and it has been used in many applications including sensors, batteries, fuel cells, supercapacitors, transistors, components of high-strength machinery, and display screens in mobile devices. In the past decade, the biomedical applications of graphene have attracted much interest. Graphene has been reported to have antibacterial, antiplatelet, and anticancer activities. Several salient features of graphene make it a potential candidate for biological and biomedical applications. The synthesis, toxicity, biocompatibility, and biomedical applications of graphene are fundamental issues that require thorough investigation in any kind of applications related to human welfare. Therefore, this review addresses the various methods available for the synthesis of graphene, with special reference to biological synthesis, and highlights the biological applications of graphene with a focus on cancer therapy, drug delivery, bio-imaging, and tissue engineering, together with a brief discussion of the challenges and future perspectives of graphene. We hope to provide a comprehensive review of the latest progress in research on graphene, from synthesis to applications. Keywords: biomedical applications, cancer therapy, drug delivery, graphene, graphene-related materials, tissue engineering, toxicity